Antibody‐virus co‐evolution in HIV infection: paths for HIV vaccine development. Issue 1 (January 2017) - Bonsignori, Mattia; Liao, Hua‐Xin; Gao, Feng; Williams, Wilton B.; Alam, S. Munir; Montefiori, David C.; Haynes, Barton F.
Summary: Induction of HIV‐1 broadly neutralizing antibodies (bnAbs) to date has only been observed in the setting of HIV‐1 infection, and then only years after HIV transmission. Thus, the concept has emerged that one path to induction of bnAbs is to define the viral and immunologic events that occur during HIV‐1 infection, and then to mimic those events with a vaccine formulation. This concept has led to efforts to map both virus and antibody events that occur from the time of HIV‐1 transmission to development of bnAbs. This work has revealed that a virus‐antibody "arms race" occurs in which a HIV‐1 transmitted/founder (TF) Env induces autologous neutralizing antibodies that can not only neutralize the TF virus but also can select virus escape mutants that in turn select affinity‐matured neutralizing antibodies. From these studies has come a picture of bnAb development that has led to new insights in host– pathogen interactions and, as well, led to insight into immunologic mechanisms of control of bnAb development. Here, we review the progress to date in elucidating bnAb B cell lineages in HIV‐1 infection, discuss new research leading to understanding the immunologic mechanisms of bnAb induction, and address issues relevant to the use of this information for the design of new HIV‐1 sequential envelope vaccine candidates.